Low arthroplasty survival after treatment for proximal humerus fracture sequelae: 3,245 shoulder replacements from the Nordic Arthroplasty Register Association - Unbehaun, Ditte; Rasmussen, Sigrid; Hole, Randi; Fenstad, Anne Marie; Salomonsson, Björn; Demir, Yilmaz; Jensen, Steen Lund; Brorson, Stig; Äärimaa, Ville; Mechlenburg, Inger; Rasmussen, Jeppe Vejlgaard (Acta orthopaedica, 2020)
Background and purpose - Proximal humerus fractures (PHF) may result in sequelae indicating arthroplasty. We report cumulative survival rates and reasons for revision after arthroplasty for proximal humerus fracture sequelae (PHFS). Patients and methods - Data were derived from the Nordic Arthroplasty Register Association. The Kaplan-Meier method was used to illustrate survival rates. A scaled Schoenfeld residual plot was used to report the risk of revision for men relative to women in patients who were treated with reverse shoulder arthroplasty (RSA). Revision was defined as removal or exchange of any component or the addition of a glenoid component. Results - 30,190 primary arthroplasties were reported from 2004 to 2016, of which 3,245 were for PHFS. The estimated 1-, 5-, and 10-year cumulative survival rates (95% CI) were 96% (95-97), 90% (89-92), and 86% (83-88) for stemmed hemiarthroplasty and 94% (92-95), 89% (87-91), and 86% (82-90) for RSA with a median time to revision of 18 months (IQR 9-44) and 3 months (IQR 0-17). The risk of revision for men relative to women in patients who were treated with RSA was 3.2 (1.9-5.1) 0-1 year after surgery and 1.9 (0.9-4.1) 1-8 years after surgery. The estimated 1-, 5-, and 10-year cumulative survival rates (95% CI) were 94% (92-96), 88% (85-90), and 80% (75-86) for men and 95% (94-96), 86% (84-89), and 81% (77-84) for young patients. Interpretation - Shoulder arthroplasty for PHFS was associated with lower survival rates, compared with previously published results of shoulder arthroplasty for acute PHF. The low arthroplasty survival rates for men and young patients especially are worrying.